MORPHOLOGICAL AND SEMANTIC ANALYSIS ON THE REGISTER USED BY K-POPERS IN ALLKPOP.COM - WAHYUDI, HAJAR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: Register, Semantic change, Word Formation ProcessesHuman as a social creature lives in the society. Human interacts and communicates to each other in the society. In to do so, human needs language. As the development of society, culture and technology, language is also develops. Language might be different depends on the location, group, culture and etc.Eventually, this leads to possibility of a word may have more than one meaning. In this study the researcher conducted a study about register used by KPopers in the Allkpop.com.There are four problems of the study, they are namelyIn this study, the researcher used qualitative approach with descriptive method. The data were the comments containing register found in the article on Allkpop.com.The researcher revealed that there were 20 kinds of register used by K- Popers. Those twenty (20) words are considered as register because they are only understandable by the K-Popers. The researcher also found6 types of word formation processes in those 20 registers used by K-Popers. They are compounding, borrowing, acronym, derivation, blending and multiple processes. Besides, the researcher also revealed that the registers could undergo three kinds of semantic change. They are generalization, specialization and total semantic change. And the last the researcher  also  revealed  the  factor  facilitating  the semantic change of the register such as needs of the new meaning and taboo word. The researcher suggests that the other students or researchers who have the same interest in sociolinguistic especially register, morphology especially word formation process or semantic especially semantic change conduct similar study using different and wider scope of data. The data could be taken from other group or  community.  Since  the  society  always  develops  and  grows  the  researcher believes that in the future there will be more and more new group / community.